A possible Buddhist influence on Chinese political thought. Issue 4 (2nd October 2018) - Barrett, T. H.
ABSTRACT: Proponents of twentieth century Chinese critiques of pre-modern Chinese autocracy could point to one or two earlier examples of negative views of autocratic rule, but the ultimate origin of these views has been hard to identify. In pre-modern Chinese accounts of the beginnings of human society, the position of ruler was generally described as an institution established as it were from above, by 'sages, ' or perhaps by Heaven. Buddhism has by contrast a more negative account of the origins of kingship as representing an expedient, collective human response to problems of social conflict. The introduction into apparently secular discourse during Tang times of an account of the origins of kingship lacking any role for 'sages' or for Heaven is therefore tentatively attributed here to tacit Buddhist influence. It is suggested that quite possibly Buddhist ideas can lie behind texts that do not exhibit Buddhist modes of expression, and that such may be the case for this author on kingship, Liu Zongyuan 柳宗元 (773–819).